Pengembangan Model Latihan Mental melalui Teknik Hypnotheraphy Berbantuan Musik Instrumental untuk Meningkatkan Konsentrasi Atlet - Adika Fatahilah; Rais Firlando (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Research purposes; (1) produce an effective training model using hypnotheraphy techniques assisted by instrumental music to increase the concentration of athletes. The test subjects were 15 male athletes from various sports in Lubuklinggau city. This study uses the reseach and development (RND) method with the following steps: (1) preparation for developing an exercise model, (2) designing a hypothetical model, (3) testing the feasibility of a hypothetical model, (4) improving the hypothetical model, (5) field testing , (6) the final product. The results of the research model are structured based on: (1) rational, (2) vision and mission of training, (3) training objectives, (4) training content, (5) system support, (6) training procedures, (7) evaluation and action and continue. The trial results were effective for increasing the concentration of athletes and there was an increase in the average score of 6.8 or 50.06%. It is reinforced by the results of the Wilcoxon test that the training model is effective for increasing the concentration of athletes. Obtained a value of 0.001 smaller than <0.05, the hypothesis can be Ha accepted. In conclusion, the developed model of hypnotheraphy technique assisted by instrumental music is effective to increase athletes' concentration Keywords: Hypnotheraphy and Instrumental Music, Concentration